Fluorinated interphase enables reversible aqueous zinc battery chemistries - Cao, Longsheng; Li, Dan; Pollard, Travis; Deng, Tao; Zhang, Bao; Yang, Chongyin; Chen, Long; Vatamanu, Jenel; Hu, Enyuan; Hourwitz, Matt J.; Ma, Lin; Ding, Michael; et al. (Nature nanotechnology, 2021)
Metallic zinc is an ideal anode due to its high theoretical capacity (820 mAh g −1 ), low redox potential (−0.762 V versus the standard hydrogen electrode), high abundance and low toxicity. When used in aqueous electrolyte, it also brings intrinsic safety, but suffers from severe irreversibility. This is best exemplified by low coulombic efficiency, dendrite growth and water consumption. This is thought to be due to severe hydrogen evolution during zinc plating and stripping, hitherto making the in-situ formation of a solid–electrolyte interphase (SEI) impossible. Here, we report an aqueous zinc battery in which a dilute and acidic aqueous electrolyte with an alkylammonium salt additive assists the formation of a robust, Zn 2+ -conducting and waterproof SEI. The presence of this SEI enables excellent performance: dendrite-free zinc plating/stripping at 99.9% coulombic efficiency in a Ti||Zn asymmetric cell for 1,000 cycles; steady charge–discharge in a Zn||Zn symmetric cell for 6,000 cycles (6,000 h); and high energy densities (136 Wh kg −1 in a Zn||VOPO 4 full battery with 88.7% retention for >6,000 cycles, 325 Wh kg −1 in a Zn||O 2 full battery for >300 cycles and 218 Wh kg −1 in a Zn||MnO 2 full battery with 88.5% retention for 1,000 cycles) using limited zinc. The SEI-forming electrolyte also allows the reversible operation of an anode-free pouch cell of Ti||Zn x VOPO 4 at 100% depth of discharge for 100 cycles, thus establishing aqueous zinc batteries as viable cell systems for practical applications. A solid–electrolyte interphase that is permeable to Zn( ii ) ions but waterproof is formed using an aqueous electrolyte composition. Cycling performances in an anode-free aqueous pouch cell show promise for intrinsically safe energy storage applications.